Development of Various Fruit Processing as a Culinary Tourism Attraction in Dokan Village, Brand District, Karo Regency - Rama Indra (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2021)
The development of processing various pineapples for the people of Dokan Village, Brand District, Karo Regency is currently something that produces added value, especially fruit farmers. The development of fruit processing into a variety of snacks and drinks has not been routinely carried out. This research is a survey research with descriptive method. The analysis technique used is to use qualitative data analysis. Referring to the results of this study where there are potentials and efforts that support the development of fruit processing as a culinary tourism attraction in Dokan Village, Brand District, Karo Regency. The Role of Karo District government efforts, in this case the Department of Agriculture, Trade, Tourism and Associations as well as educational institutions have carried out training activities for the development of fruit processing into a variety of processed food and beverages. Another effort by the Karo Regency government is to make Dokan Village, Brand District, Karo Regency into a village based on Agro-tourism and Culinary Tourism.